Effective Intervention Strategies to Improve Health Outcomes for Cardiovascular Disease Patients with Low Health Literacy Skills: A Systematic Review - Tae Wha Lee, RN, PhD; Seon Heui Lee, RN, PhD; Hye Hyun Kim, RN, MSN; Soo Jin Kang, RN, PhD (Elsevier, 2012)
Purpose: Systematic studies on the relationship between health literacy and health outcomes demonstrate that as health literacy declines, patients engage in fewer preventive health and self-care behaviors and have worse disease-related knowledge. The purpose of this study was to identify effective intervention strategies to improve health outcomes in patients with cardiovascular disease and low literacy skills. Methods: This study employs the following criteria recommended by Khan Kunz, Keijnen, and Antes (2003) for systematic review: framing question, identifying relevant literature, assessing quality of the literature, summarizing the evidence, and interpreting the finding. A total of 235 articles were reviewed by the research team, and 9 articles met inclusion criteria. Although nine studies were reviewed for their health outcomes, only six studies, which had a positive quality grade evaluation were used to recommend effective intervention strategies. Results: Interventions were categorized into three groups: tailored counseling, self-monitoring, and periodic reminder. The main strategies used to improve health outcomes of low literacy patients included tailored counseling, improved provider-patient interactions, organizing information by patient preference, self-care algorithms, and self-directed learning. Specific strategies included written materials tailored to appropriate reading levels, materials using plain language, emphasizing key points with large font size, and using visual items such as icons or color codes. Conclusion: With evidence-driven strategies, health care professionals can use tailored interventions to provide better health education and counseling that meets patient needs and improves health outcomes.